(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
From kirana shop retailing to internet retailing (i.e., rural to urban), the Indian retailing sector has evolved. This situation was disorganized at first, but it is now evolving into Omnichannel commerce through Social Media (Facebook). The goal of this research is to provide a more intelligent shopping experience on social media, particularly on Facebook. The Random Sampling technique was used to gather data from 1045 respondents using the Structured Questionnaire. Madurai Engineering Students and Staff are among the responses. The data was analyzed using Statistical Software (SPSS), with simple percentages, descriptive statistics, and ANOVA being utilized to analyze the data. This research provides a comprehensive explanation and analysis of how Facebook affects the business dynamics of retailers.